2022
DOI: 10.3390/ijms231911972
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Vitellogenin and Its Receptor in Spodoptera frugiperda (J. E. Smith, 1797), and Their Function in Reproduction of Female

Abstract: The fall armyworm Spodoptera frugiperda is a highly polyphagous invasive pest. The strong reproductive capacity is an important factor in the rapid colonization and expansion of S. frugiperda. Vitellogenin (Vg) and vitellogenin receptor (VgR) play important roles in insect reproduction. As the precursor of vitellin (Vn), Vg provides essential nutrition for embryonic development, and VgR mediates the uptake of Vg by oocytes. In this context, we cloned and characterized these two genes of S. frugiperda (SfVg and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…Interestingly, silencing of Vg genes appears to interfere with EcVgR expression. This feedback loop has also been reported in S. frugiperda (Han, Wang, et al, 2022), although it is not common across insects (Hu et al, 2019; Lu et al, 2015). Finally, treatment with ds VgR silenced EcVgR but did not interfere with EcVg1 or EcVg2 expression after 48 h. The feedback loop here is not evident but cannot be excluded since, when VgR was knocked down in S. frugiperda , the expression of Vg decreased compared to that in the control after 72 h (Han, Wang, et al, 2022).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Interestingly, silencing of Vg genes appears to interfere with EcVgR expression. This feedback loop has also been reported in S. frugiperda (Han, Wang, et al, 2022), although it is not common across insects (Hu et al, 2019; Lu et al, 2015). Finally, treatment with ds VgR silenced EcVgR but did not interfere with EcVg1 or EcVg2 expression after 48 h. The feedback loop here is not evident but cannot be excluded since, when VgR was knocked down in S. frugiperda , the expression of Vg decreased compared to that in the control after 72 h (Han, Wang, et al, 2022).…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, given that the pattern of gene expression can be associated with physiological functions (Han, Wang, et al, 2022), we examined the expression levels of EcVg1 , EcVg2, and EcVgR in females of different ages. In E. connexa , female sexual maturity typically occurs approximately 5–6 days after emergence (DAE) (Silva et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may have been because of the differences in the physiological functions and morphological structures between larvae and pupae in Lepidoptera insects, resulting in different affinities of the three compounds for trehalase in the larvae and pupae. Multiple studies have demonstrated that vitellogenesis can directly affect insect reproduction and is essential when studying reproductive regulation [52][53][54]. The expression of SfVg and SfVgR in the female adults of the treatment group in our study exhibited significant upregulation and downregulation, respectively, on the fourth day of eclosion.…”
Section: Discussionmentioning
confidence: 55%